DIPLOMASI BUDAYA MELALUI KARAKTER YUN JIN DARI VIDEO GAME GENSHIN IMPACT SEBAGAI UPAYA PERWUJUDAN CHINESE DREAM - Achmad Fadillah Moeslem (2024)
This research aims to find out how HoYoverse, with Yun Jin in the video game Genshin Impact, contributes to Xi Jinping's Chinese Dream vision. This research uses the concepts of soft power, public diplomacy, cultural diplomacy, and national branding. The research method used is descriptive qualitative to explain cultural diplomacy by non-state actors with the HoYoverse case study. The data collection techniques used are library research and studying documentation. The data analysis technique uses the Miles and Huberman method, namely data reduction, data presentation, and drawing conclusions and verification. The research results show that the Chinese Dream initiated by Xi Jinping is quite focused on Chinese culture so that this also influences regulations in the video game industry. HoYoverse, as the developer and publisher of Genshin Impact, contributes to the Chinese Dream through cultural diplomacy where HoYoverse, through Yun Jin, spreads one of China's cultural heritage, namely Peking Opera. The success experienced by Genshin Impact has helped the spread of Peking Opera.